Applications of quadratic D-forms to generalized quadratic forms - Amir Hossein Nokhodkar (پژوهش‌های ریاضی, 2022)
In this paper, we study generalized quadratic forms over a division algebra with involution of the first kind in characteristic two. For this, we associate to every generalized quadratic from a quadratic form on its underlying vector space. It is shown that this form determines the isotropy behavior and the isometry class of generalized quadratic forms.